2017
DOI: 10.1126/science.aah4307
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 promotes lineage plasticity and antiandrogen resistance in TP53 - and RB1 -deficient prostate cancer

Abstract: Some cancers evade targeted therapies through a mechanism known as lineage plasticity, whereby tumor cells acquire phenotypic characteristics of a cell lineage whose survival no longer depends on the drug target. We use in vitro and in vivo human prostate cancer models to show that these * Corresponding author. sawyersc@mskcc.org. SUPPLEMENTARY MATERIALS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
916
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 858 publications
(1,018 citation statements)
references
References 41 publications
58
916
0
Order By: Relevance
“…49,118,119). The induction of lineage plasticity by N-MYC is also consistent with data from prostate epithelial cells engineered with a loss of RB1 or TP53 (120)(121)(122). A lineage switch driven by N-MYC induction appears to afford the tumor cells the ability to escape cell death induced by anti-AR therapy.…”
Section: Hematologic Malignanciessupporting
confidence: 80%
See 1 more Smart Citation
“…49,118,119). The induction of lineage plasticity by N-MYC is also consistent with data from prostate epithelial cells engineered with a loss of RB1 or TP53 (120)(121)(122). A lineage switch driven by N-MYC induction appears to afford the tumor cells the ability to escape cell death induced by anti-AR therapy.…”
Section: Hematologic Malignanciessupporting
confidence: 80%
“…As noted above, EZH2 has been shown to cooperate with N-MYC as a transcriptional coregulator to drive CRPC toward an NEPC phenotype (46). Treatment with EZH2 inhibitors reverses N-MYC-driven target gene expression and abrogates tumor cell growth driven either by N-MYC (46) or other drivers of the NEPC phenotype (120,121). Given the availability of EZH2 inhibitors that are now in phase I clinical trials for advanced solid tumors (e.g., NCT02082977), this characterization will potentially provide a rationale for further clinical development for patients with N-MYC-overexpressed NEPC and CRPC.…”
Section: Targeting N-myc Transcriptional Functionmentioning
confidence: 95%
“…To expand analyses of the RB pathway to recent clinical findings, alterations in the androgen receptor (AR), RB, cyclin-CDK, and CDK inhibitor profiles were assessed using a cohort of CRPC tissue from the Stand Up to Cancer/Prostate Cancer Foundation (SU2C/PCF) prostate cancer collection ( Figure 1, A and B, and ref. 39). As expected based on the known role of the AR in promoting disease progression (40), AR amplification was observed in 30.5% (44/144) of tumors analyzed.…”
Section: Rb/e2f1 Pathway Disruption Is Frequent In and Preferentiallymentioning
confidence: 51%
“…Importantly, higher stringency used to define differentially expressed genes in the model systems used herein identified stronger concordance between in vitro expression data and gene expression profiles from patient tumor samples, further highlighting the clinical relevance of the targets identified in these models. It is of note that the current study used models of AR-positive disease in addition to non-neuroendocrine CRPC tumor samples (SU2C/PCF), as recent studies suggest that RB loss may yield distinct effects in tumors acquiring neuroendocrine phenotypes via RB loss (39,87). Further, as RB loss of expression has been shown in the current study to elicit molecular effects distinct from those driven by phosphorylation-induced inactivation, it is likely that this RB loss-induced gene signature (E2F1 expanded signature) could be applied to other disease types to indicate similar E2F1 reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have begun to shed light on key drivers of neuroendocrine differentiation that include the involvement of developmental transcription factors such as SOX2 that serve to influence self-renewal and pluripotency, and epigenetic modifiers such as EZH2 that influence embryonic development and cell proliferation (6,7). In this context, Zou and colleagues found that Sox11, a member of the SOXC subclass of HMG-box transcriptional regulators, was upregulated in treatment-resistant NPp53 tumors.…”
mentioning
confidence: 99%